EFFECTIVENESS, OUTCOME, AND SAFETY OF VITAMIN D SUPPLEMENTATION IN PATIENTS WITH PSORIASIS: A COMPREHENSIVE SYSTEMATIC REVIEW - Yulianto, Ronald; Aristika Gunawan, Ellen (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Insights into psoriasis as a systemic ailment have spurred the investigation of novel therapies due to dissatisfaction with current treatments and significant quality of life impairment. Vitamin D3 deficiency is implicated in psoriasis pathophysiology, with studies highlighting its impact on keratinocyte regulation and autoimmune disease resistance. This review critically evaluates evidence on high-dose oral vitamin D3 supplementation for psoriasis management, aiming to assess its effectiveness, treatment outcomes, and safety profile to inform clinician. Methods: This systematic review focused on full-text English literature published between 2017 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Our research team initially collected numerous publications from credible sources such as Science Direct, PubMed, and JAMA Dermatology. Employing a meticulous three-tier screening approach, we identified only five papers that were directly pertinent to our ongoing systematic assessment. Subsequently, we conducted a comprehensive examination of the entire text and further selected articles; case control study, double-blind, randomized, placebo-controlled study, randomized controlled trial, a bidirectional two-sample mendelian randomization analysis, and observational cross-sectional study. Conclusion: In conclusion, maintaining serum vitamin D levels above 30 ng/ml may benefit severe psoriasis, while oral vitamin D2 supplementation showed promise in mild cases. Larger trials are needed for severe psoriasis, and future research should explore higher doses. Additionally, a study found no support for monthly vitamin D3 supplementation in older mild psoriasis patients. We confirmed the causal link between vitamin D levels and psoriasis, identified associations with increased risk, and explored effects on atopic dermatitis. While no significant difference was found in serum vitamin D levels between psoriasis patients and controls, lower levels in psoriasis suggest various influences.